(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the efficacy and safety of radiofrequency ablation in the treatment of benign thyroid nodules at Phuong Bac General Hospital. Methods: A retrospective descriptive study was conducted on 20 patients using a pre-post treatment design. Data were collected at two time points: baseline (pre-treatment) and 12 months post-radiofrequency ablation. The study was carried out at Phuong Bac General Hospital from August 2023 to December 2024. Results: The mean age of the study population was 49.7 years. At the 12-month follow-up post-radiofrequency ablation: the mean symptom score (scale 0-10) decreased from 3.53 at baseline to 1.02; the mean cosmetic score (scale 1-4) decreased from 3.1 to 1.5. The mean nodule volume decreased from 4.92 mL at baseline to 1.04 mL, corresponding to a mean volume reduction rate of 78.9%. All recorded complications were mild and self-limiting. Specifically, one patient experienced pain in the right jaw and right hemicranium, which resolved spontaneously post-procedure; one patient had a minor neck hematoma that required no intervention; and one patient experienced transient hoarseness during the procedure with immediate recovery. Additionally, three patients presented with subclinical hyperthyroidism one week post-radiofrequency ablation but returned to a euthyroid state after one month. Conclusion: Radiofrequency ablation is a safe and effective minimally invasive procedure for treating benign thyroid nodules, providing significant volume reduction, clinical symptom relief, and improved cosmetic outcomes.